Amisulpride versus Risperidone in the Treatment of Acute Exacerbation of Schizophrenia - Ranjan, S; Vyas, JN (Journal of Universal College of Medical Sciences, 2013)
Introduction: Amisulpride and risperidone are both atypical antipsychotic having different receptor affinity characteristics. Although there are many studies comparing the efficacy of both drugs with conventional antipsychotics, studies comparing the efficacy of amisulpride with risperidone are less. There are no such studies published till yet from Nepal. This study aims to compare the efficacy and safety of amisulpride with that of risperidone in patients with acute exacerbation of schizophrenia in Nepal. Methods: 100 patients with acute exacerbation of schizophrenia were randomly put on flexible dose of amisulpride (200-1000mg/day) or risperidone (2-10mg/day) for six weeks after three to six day placebo wash-out period. Efficacy was assessed by changes in score of Brief Psychiatry Rating Scale (BPRS). Safety assessment was done by adverse event reporting, physical examination, blood pressure, heart rate monitoring and applying modified Simpson-Angus Scale for extra pyramidal symptoms. Results: Most of the patients in both group responded equally to medication. 84% of amisulpride receiving patients versus 86% in risperidone group responded to treatment. Both drugs were safe and caused comparable extra pyramidal symptoms (amisulpride/risperidone: 14/16). However, risperidone caused more weight gain than amisulpride (64% vs. 12%). Conclusion: Amisulpride and risperidone are equally effective in the treatment of acute exacerbation of schizophrenia. Both drugs were well tolerated. Amisulpride was associated with less weight gain. DOI: http://dx.doi.org/10.3126/jucms.v1i1.8417 Journal of Universal College of Medical Sciences Vol.1(1) 2013: 15-19